Overexpression of miR-3653 is Associated with HPV Infection and Serves as a Biomarker in Patients with Cervical Cancer - Cui H; Zhang B; Ruan M; Fang C; Li N; Sun X; Qi J; Zuo R; Zhang S; Rong J (Dove Medical Press, 2022)
Haiyan Cui,1 Baohua Zhang,2 Mei Ruan,3 Chunmei Fang,4 Ning Li,5 Xiaoqin Sun,6 Junmei Qi,1 Rongrong Zuo,1 Shuangshuang Zhang,1 Jiansheng Rong2 1Pathology Department, The Fourth People Hospital of Zibo, Zibo, Shandong, 255067, People's Republic of China; 2Pathology Department, Zibo Central Hospital, Zibo, Shandong, 255036, People's Republic of China; 3Oncology Department, The Fourth People Hospital of Zibo, Zibo, Shandong, 255067, People's Republic of China; 4Gynecology Department, Zibo Lianchi Women & Infants Hospital, Zibo, Shandong, 255000, People's Republic of China; 5Department of Physical Examination, Zichuan Traditional Chinese Medicine Hospital, Zibo, Shandong, 255100, People's Republic of China; 6Pathology Department, Zibo Maternal and Child Health Hospital, Zibo, Shandong, 255000, People's Republic of ChinaCorrespondence: Jiansheng Rong, Pathology Department, Zibo Central Hospital, No. 54 Gongqingtuan West Road, Zibo, Shandong, 255067, People's Republic of China, Tel/Fax +86 533-2360321, Email rongjiansheng_zbzx@163.comBackground: Human papillomavirus (HPV) is a major cause of cervical cancer (CC) occurrence. This study aimed to explore whether abnormal microRNA (miR)-3653 is associated with HPV infection and to investigate the clinical value of miR-3653 in the diagnosis and prognosis of CC.Methods: Tumor tissues and adjacent non-cancerous tissues were collected from 136 patients with CC. Cervical tissues from 101 patients with uterine fibroids were collected as controls. The expression of miR-3653 was measured by quantitative real-time PCR. The ability of miR-3653 to discriminate between HPV positive (HPV+) and HPV negative (HPV-) CC patients, and to discriminate patients from controls was assessed by receiver operating characteristic analysis. Kaplan-Meier curves and Log rank tests were used to evaluate the relationship of miR-3653 with survival of CC patient. Whether miR-3653 could function as a prognostic indicator was evaluated by univariate and multivariate Cox analyses.Results: miR-3653, highly expressed in CC tissues, was associated with HPV infection, tumor diameter, International Federation of Gynecology and Obstetrics (FIGO) stage and lymph node metastasis in CC patients. Additionally, miR-3653 was increased in HPV+ controls, CC patients and CC cells. Moreover, miR-3653 could screen HPV+ controls, screen HPV+ patients and screen CC patients. Furthermore, miR-3653 was associated with the survival of CC patients (log-rank P < 0.001) and could serve as an independent prognostic indicator for CC patients.Conclusion: miR-3653, increased in CC, is related to HPV infection and may serve as a diagnostic and prognostic biomarker for CC patients.Keywords: miR-3653, microRNA, HPV, cervical cancer, diagnosis, prognosis